2013
DOI: 10.7567/apex.6.077302
|View full text |Cite
|
Sign up to set email alerts
|

Local Modification of Cu Microwires by Joule Heating

Abstract: A technique for modifying the crystalline structure of a metallic microwire is introduced. The technique involves passing current through the wire via two electrical probes causing local Joule heating. We used this technique to heat a 25-µm-diameter Cu wire for 1 h at 573 K. The yield stress of the wire after modification was evaluated by a mechanical bending test and it was confirmed that the wire had softened after the process. We also performed heat treatment of a wire in a furnace and the properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Joule-heating by supplying a current to wire is known to be an effective method for the heat treatment of thin wire [13][14][15][16][17][18][19]. Because copper has a small heat capacity (0.385 J/g o C), the temperature of small-scale copper wire can be easily increased by passing a current [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joule-heating by supplying a current to wire is known to be an effective method for the heat treatment of thin wire [13][14][15][16][17][18][19]. Because copper has a small heat capacity (0.385 J/g o C), the temperature of small-scale copper wire can be easily increased by passing a current [20].…”
Section: Introductionmentioning
confidence: 99%
“…Because copper has a small heat capacity (0.385 J/g o C), the temperature of small-scale copper wire can be easily increased by passing a current [20]. It has been reported that normal copper wires can be softened by Joule-heating [19,20], and that grains grow faster than with heat treatment using a conventional furnace [13,20]. Tohmyoh et al [20] reported that during the Joule-heating of copper microwires, yield strength decreased as the grain size increased.…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of Cu microwires are sensitive to the crystalline structure 27)- 32) , and thus, controlling the structure of the wire is a useful way of enabling the wires to be used for various purposes. It has been reported that Cu microwires can be softened by Joule heating 25) , and that the Cu grains grow faster by Joule heating compared with the heat treatment with a conventional furnace 26) .…”
Section: Introductionmentioning
confidence: 99%
“…Of the available techniques for joining small scale materials together, that utilizing Joule heat can be used in various situations to join micro or nanowires (Tohmyoh, et al, 2007) or carbon nanotubes (Hirayama, et al, 2001;Dong, et al, 2007;Jin, et al, 2007), etc. Joule heat has also been used to solder nanowires (Peng, et al, 2009) and to structurally modify thin wires (Hummelgård, et al, 2010;Tohmyoh and Ishihara, 2013).…”
Section: Introductionmentioning
confidence: 99%